Successful management plan of COVID-19 in a pediatric hemato-oncology department: a single-centre experience - Giuseppe Menna; Pio Stellato; Annalisa Granata; Antonia De Matteo; Carlo Capelli; Matteo Paparo; Rosanna Parasole; Immacolata Ricciardi; Francesco Paolo Tambaro; Ornella Leone; Lucia Quaglietta; Nicola Silvestri (BMJ Publishing Group, 2020)
COVID-19 pandemic raised concern about management of patients with paediatric cancer. We present the operating system that the Hemato-Oncology Department of the Santobono-Pausilipon Hospital applied. We divided our department in three zones: surveillance and screening; quarantine and COVID free, in order to screen admitted patients and to reduce the risk of cross infection. From 3 April until 29 May 2020 (56 days), 662 patients and caregivers underwent rapid serological tests for a total of 1397 assays. No patient or parent with SARS-CoV2 infection was found, demonstrating the effectiveness of COVID-19 screening process.